Synthesis, Characterization, Antibacterial and Free Radical Scavenging Activities of Some New 1,2,4-triazole Schiff Bases and Mannich Bases - Sim, Kooi-Mow; Loo, Siew-Theng; Teo, Kah-Cheng (Letters in Organic Chemistry, 2014)
The synthesis of a series of 1,2,4-triazole Schiff bases and Mannich bases incorporating an indole moiety is described. The triazole Schiff bases were synthesized from 4-amino-3-mercapto-5-[(1H-indol-3-yl)methyl]-1,2,4-triazole on treatment with a series of arylaldehyde in presence of (+)-tartaric acid as an acidic catalyst. The triazole Schiff bases are further condensed with piperidine and formaldehyde to yield the corresponding series of Mannich bases. The structures of Schiff bases and Mannich bases were established by IR, NMR and mass spectral data. All the synthesized compounds were screened for their antibacterial and free radical scavenging activities. Schiff base 2d comprising of dichloro substitution exhibited promising antibacterial activity against Bacillus subtilis spizizenni, Bacillus cereus and Staphylococcus aureus at MIC 7.81 μg/ml. Mannich bases demonstrated weak free radical scavenging activity when compared to their Schiff base counterparts.
Keywords: 2